2016
DOI: 10.1002/ldr.2549
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Nutrient Losses in a Flat Land‐Reclamation District of Central Italy

Abstract: Erosion and nutrient losses represent two of the most important environmental impacts of agriculture. In a field experiment, we compared the impact and productivity of three continuous maize-cropping systems-conventional, low input and environmentally protective-on two contrasting soils (peat and loam soil) within a flat land-reclamation district of Central Italy. This area is characterized by intensive agriculture and the presence of a receiving eutrophic lake. Cumulative runoff, sediment, dissolved and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The PHUSICOS NBS interventions to be implemented in Italy are located in private land near Lake Massaciuccoli in the region of Tuscany (Figure 6) and are focused on reducing runoff from farmland, with erosion and transport of sediments and pollutants to the aquatic environment [14]. The area is located south-east of Lake Massaciuccoli, a lake roughly at sea level, whereas the areas for the NBS are 1-2 m below sea level and kept dry by a system of pumping stations.…”
Section: Serchio River Basin Italymentioning
confidence: 99%
“…The PHUSICOS NBS interventions to be implemented in Italy are located in private land near Lake Massaciuccoli in the region of Tuscany (Figure 6) and are focused on reducing runoff from farmland, with erosion and transport of sediments and pollutants to the aquatic environment [14]. The area is located south-east of Lake Massaciuccoli, a lake roughly at sea level, whereas the areas for the NBS are 1-2 m below sea level and kept dry by a system of pumping stations.…”
Section: Serchio River Basin Italymentioning
confidence: 99%
“…Agriculture is one of the main causes of the desertification of the land, and this is partially due to the exhaustion of the soil nutrients (Kraaijvanger & Veldkamp, 2015;Lü et al, 2016;Lucas-Borja et al, 2016;Udeigwe et al, 2016). There is a need to restore the degraded lands (Chen et al, 2016;Costantini et al, 2016), and the recovery of the nutrients is a key strategy (Gronwald et al, 2015;Silvestri et al, 2016;Wang et al, 2016a). Potassium (K) is an essential element for higher plants; it plays a particularly crucial role in a number of physiological processes vital to growth, yield, quality and stress resistance of all crops (Pettigrew, 2008;Römheld & Kirkby, 2010;Zörb et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…) with a clay content <10%. Studies showed that soils with lower clay and silt contents and bulk density experience more soil erosion (Silvestri et al, 2017;Ouyang et al, 2018). One of the main factors controlling the soil erosion is related to the land use (Sharma et al, 2011).…”
Section: Impacts Of the Land Use On Soil Erosionmentioning
confidence: 99%